(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Present work discusses about the design and simulation of a 405kwp solar PV system in Galgotias college of Engineering & Technology. The goal is to evaluate the potential of solar energy to provide sustainable and environmentally friendly electricity in the college which is integrated to grid. This system uses 580W PV module and 380kW invertor. We analyzed the system using PVsyst,solargis and SketchUp. The result showed that SOLARGIS estimated annual energy generation between 550 MWh and 555 MWh. While PVsyst provided a higher estimate of 579.4MWh. This indicates that PVsyst predicts more energy output then the other tools.